Continuous heterogeneous isomerization of 3/4-methyltetrahydrophthalic anhydride (3/4-MTHPA) with acid- and base-modified γ-Al2O3 catalysts. (15th December 2022) - Yin, Lei; Li, Hui Yang; Ge, Tingting; Li, Yuchao; Zuo, Cuncun; Wang, Ming; Cui, GuangJun; Huang, Haofei; Guo, Lin
Abstract : A series of tests and isomerization experiments were carried out to determine the activity and life of the catalyst. Abstract : A series of acid–base-loaded γ-Al2 O3 catalysts was applied as the catalysts for the isomerization of 3/4-methyl-tetrahydro phthalic anhydride. With a basic metal (K or Na) as the basic source and phosphorus (P) as the acid source, γ-Al2 O3 was modified by equal volume immersion. NH3 /CO2 -TPD, XRD, TEM/EDS, BET, and TGA were used to analyze the catalysts, and 15%-K/Al2 O3 and 10%-P/Al2 O3 were determined as the most appropriate catalysts. The isomers were qualitatively and quantitatively analyzed using nuclear magnetic resonance ( 1 H-NMR) and infrared spectroscopy (IR), and the reaction mechanism for the isomer formation was proposed. With 3-MTHPA as the substrate, the acid/base reaction temperature was 165/150 °C, the reaction time was 3 h and the amount of the catalyst added was 3%. A new type of continuous isomeric fixed-bed reactor was designed. The stability of the catalyst was tested, and the activity loss was 4.6–6.6% after 10 hours of operation.